In situ forming implants: Component, formation mechanisms, and pharmaceutical applications - Keyang Ni; Haojie Yu; Li Wang; Yuan Meng (Chemical Engineering Journal, 2026)

Improving drainage and structural uniformity of soft soil via freeze-thaw method - Jintao Hu; Hu Zhang; Bo Zheng; Cheng Wen; Keyang Wang; Ze Zhang; Shengrong Zhang; Andrei Zhang; Mikhail Zhelezniak (Cold Regions Science and Technology, 2026)

A mechanically robust, fully zwitterionic photothermal hydrogel with superhydrated interfaces for antifouling desalination - Keyang Shen; Yunpeng Zhu; Haiyang Wang; Jingtao Bi; Lei Wang; Zhiyuan Guo; Jing Wang; Panpan Zhang; Zhi-Yong Ji (Chemical Engineering Journal, 2026)

Cellulose/polyester-blended microplastics amplify plastisphere pathogen and antibiotic resistome risks - Keyang Jiang; Xinru Pan; Sijia Zhu; Zewen Dang; Zhenzhen Yang; Liangyu Huang; Xiaochen Pan; Xuelian Zou; Jian Zhang; Yanzhu Guo; Wei Zhang; Zhi Li; et al. (Bioresource Technology, 2026)

Cloning and functional verification of genes LjHD8 and LjMIXTA1 related to trichome development in Lonicera japonica Thunb. - Xinrui Fan; Jing Fu; Qiu Jiang; Keyang Zhang; Yongqing Zhang; Lingna Wang (Planta, 2026)

Corrigendum to “Mechanisms of structural weakening and interfacial reconfiguration in the adsorption of methane from bituminous coal by anaerobic microorganisms in the presence of CO2” [Fuel 428 (2027) 140504] - Yundu Yang; Bingjun Liu; Junyu Wang; Sheng Xue; Chao Zhang; Yongqiang Yang; Keyang Cheng; Fengrong Wu; Wenshuai Ma (Fuel, 2026)

Inhibition and flotation of anaerobic granular sludge induced by long-chain fatty acid sodium salts - Qian Gao; Sijia Zhu; Keyang Jiang; Wenxia Zhai; Peng Lu; Qiulin Yang; Wei Zhang; Hainong Song; Zhiwei Wang (Journal of Environmental Chemical Engineering, 2026)

Plasmonic magnetic nanoparticle-based photothermal sensor for sensitive detection of chlorantraniliprole - Zongyou Chen; Keyang Lai; Aoxue Wang; Jiaqi Yin; Juan Peng; Weihua Lai (Food Chemistry, 2026)

A 500-year cycle of demographic expansion and contraction in the lower Yangtze and adjacent coastal region during the Holocene driven by East Asian summer monsoon oscillations - Deke Xu; Yuhai Wang; Keyang He; Hao Li; Yajie Dong; Jun Kuang; Zhigang Zhang; Bing Song; Yulong Niu; Guoping Sun; Yonglei Wang; Jiatong Lu; et al. (Quaternary Science Reviews, 2026)

Insights into the effects of different nitrogen sources on microbial metabolic function and biodegradation of bituminous coal - Yundu Yang; Bingjun Liu; Sheng Xue; Junyu Wang; Xiangqing Jiang; Ruifeng Chen; Rui Sun; Keyang Cheng (Fuel, 2026)

Biomass aerogel doped with FeS₂/MoS₂-modified anode for enhanced bioelectricity generation in microbial fuel cell and efficient treatment of high-concentration wastewater - Wenxia Zhai; Qian Gao; Ling Liu; Keyang Jiang; Sijia Zhu; Junxia Ni; Kaize Zhao; Wei Zhang; Zhaodong Qiu; Xi Liu; Zhiwei Wang (Journal of Environmental Chemical Engineering, 2025)

Unveiling role of accumulation by various submerged plants in removal of per- and polyfluoroalkyl substances from reclaimed water - Lin Chen; Qian Wang; Yuanyuan Li; Xin Shan; Keyang Wu; Cuizhu Sun; Lingyun Chen; Fengmin Li (Bioresource Technology, 2025)

Cadmium exposure and health outcomes:An umbrella review of meta-analyses - Wenzhuo Xu; Sainan Wang; Wenhua Ruan; Mingyue Hao; Kele Jiang; Hao Guo; Anyi Geng; Mengting Man; Zheng Hu; Yun Liu; Guifang Jin; Haiyan Shi; et al. (Environmental Research, 2025)

Longitudinal reconfiguration of multifaceted fish α and β diversity triggered by non-native species invasion in tropic rivers of Hainan Island - Dangen Gu; Chi Zhang; Gaojun Li; Meng Xu; Hui Wei; Miao Fang; Lu Shu; Xuejie Wang; Keyang Peng; Zhongguan Jiang; Fandong Yu (Journal of Environmental Management, 2025)

Target-Defense Games with One or Two Unmanned Surface Vehicles Defending an Island: A Geometric Analytical Approach - Keyang Wang; Yintao Wang; Qi Sun (Journal of Marine Science and Engineering, 2025)
This paper considers a target-defense game in an open area with one or two defenders as well as an intruder. The intruder endeavors to reach the boundary of the island, while the defenders strive to prevent that by capturing the intruder through contact. Islands, as closed areas, restrict the free movement of the defenders, since the defenders—represented by USVs—cannot traverse the target area directly. First, we are concerned with the barrier, which is the boundary of the winning zones, taking into account the impact of the target. For the initial states lying in the defenders’ winning zone, there exists a strategy for the defenders to intercept the intruder regardless of the intruder’s best effort, while for the initial states lying in the intruder’s winning zone, the intruder can always invade successfully. We propose a geometric method to construct the barrier analytically for two kinds of speed ratios. Then, by taking index functions into consideration, we present optimal strategies for the players after constructing the dominance regions when their initial states lie in different winning zones. Simulation results verify the effectiveness of the proposed method. This study can be extended to scenarios involving multiple defenders.

Design of Ni-based heterostructured catalyst with Ni3+ for enhanced bidirectional sulfur conversion - Yurui Wu; Wei Li; Hengzhi Liu; Yufang Chen; Manfang Chen; Xingqiao Wu; Yunfeng Peng; Wenlong Xia; Yuchao Du; Keyang Fu; Xiukang Yang; Xianyou Wang; et al. (Chemical Engineering Journal, 2025)

Urea-hydrolyzing Bacillus pasteurii microbially induced calcite precipitation for Ca2+ removal and enhanced anaerobic granular sludge activity in high-calcium wastewater - Jinhu Feng; Wenhao Dang; Qian Gao; Keyang Jiang; Sijia Zhu; Junxia Ni; Jian Zhang; Peng Lu; Weiqi Wei; Hainong Song; Xi Liu; Zhiwei Wang (Journal of Water Process Engineering, 2024)

Impact of phenolic-formaldehyde resin microplastics on anaerobic granular sludge: EPS interaction mechanisms and impacts on reactor performance - Keyang Jiang; Qian Gao; Jinhu Feng; Sijia Zhu; Wenxia Zhai; Di Wu; Huiya Zhang; Wei Zhang; Xi Liu; Jian Zhang; Shuangfei Wang; Zhiwei Wang (Journal of Hazardous Materials, 2024)

Exogenous signaling molecules N-acyl-homoserine lactones promotes the reconstruction of sludge particles after impact with highly concentrated urea-formaldehyde resin microplastics - Keyang Jiang; Xiao Yang; Qian Gao; Junxia Ni; Jinhu Feng; Di Wu; Xuelian Zou; Li Hu; Xi Liu; Zhaoping Song; Zhiwei Wang (Journal of Environmental Management, 2024)

Surface free radicals activated CoP/MoS2 sensors through electrocatalytic water splitting for enhanced NO2 sensing at room temperatures - Xixi Li; Xiao Wang; Zhaokun Sun; Feifei Li; Yao Fu; Keyang Zhao; Gang Zhao; Cunguang Zhu; Xijin Xu (Chemical Engineering Journal, 2024)

Synergetic effect of biochar and intermittent electricity stimulation on mitigating the adverse effects of tannic acid on anaerobic granular sludge in wastewater - Junxia Ni; Yihu Xu; Keyang Jiang; Ling Liu; Yunpeng Zhu; Xuelian Zou; Qian Gao; Jinhu Feng; Di Wu; Xiaopeng Yue; Wei Zhang; Shuangfei Wang; et al. (Journal of Water Process Engineering, 2024)

Transitional bimetallic heterostructure catalyst modified anode for microbial fuel cell treatment of high-intensity wastewater - Ling Liu; Keyang Jiang; Yunpeng Zhu; Kaili Zhu; Xuelian Zou; Qian Gao; Junxia Ni; Jinhu Feng; Di Wu; Zhiwei Wang; Cuiping Mao (Journal of Environmental Chemical Engineering, 2024)

Geographic mosaics of rice domestication in the lower Yangtze River indicated by morphological characteristics of rice bulliform phytoliths - Keyang He; Yonglei Wang; Yunfei Zheng; Guoping Sun; Shao Lei; Yongning Li; Xiaoshan Yu; Jianping Zhang; Houyuan Lu (Archaeological and Anthropological Sciences, 2024)

Ros-responsive dextran-phenylboronic acid-silibinin nanoparticles for targeting delivery of BAPTA-AM to effectively eliminate calcium overload-mediated inflammatory cascades and mitochondrial apoptosis: Alleviating acute liver injury - Yanan Wang; Huichao Wei; Keyang Li; Liru Liu; Yingfei Zhu; Xinyuan Wang; Jiahui Yan; Liangmin Yu; Xuefeng Yan; Zhiyu He (Chemical Engineering Journal, 2024)

Risk identification and assessment methods of offshore platform equipment and operations - Keyang Liu; Baoping Cai; Qibing Wu; Mingxin Chen; Chao Yang; Javed Akbar Khan; Chenyushu Wang; Hasini Vidumini Weerawarna Pattiyakumbura; Weifeng Ge; Yonghong Liu (Process Safety and Environmental Protection, 2023)

Physical properties of natural deep eutectic solvent and its application in remediation of heavy metal lead in soil - Kaiming Kang; Xiaoqiao Jia; Keyang Zheng; Xinyu Wang; Baoyou Liu; Yongjiang Hou (Journal of Contaminant Hydrology, 2023)

Review of the mechanism and control methods of anaerobic granular sludge calcification - Zhiwei Wang; Keyang Jiang; Yunpeng Zhu; Ling Liu; Xuelian Zou; Xiao Yang; Yihu Xu; Jian Zhang; Yubao Chen; Wenhua Gao; Shuangfei Wang (Journal of Water Process Engineering, 2023)

Nicosulfuron on the Atrazine-degrading Arthrobacter sp. DNS10 by assays of intracellular accumulation of substrates, Zeta potential, EPS, and stress responses - Shijie Deng; Qihang Zhou; Yuying Wang; Yuxin Liu; Keyang Xia; Bo Cao; Zhao Jiang; Ying Zhang (International Biodeterioration & Biodegradation, 2023)

Construction and characterization of Pickering emulsions stabilized by soy protein hydrolysate microgel particles and quercetin-loaded performance in vitro digestion - Jinjie Yang; Bin Zhu; Keyang Lu; Jingjing Dou; Yijie Ning; Huan Wang; Yang Li; Baokun Qi; Lianzhou Jiang (Food Research International, 2023)

Tuning interfacial microstructure of alginate-based amphiphile by dynamic bonding for stabilizing Pickering emulsion - Shuntian Huang; Zhaojun Wang; Qichang Zhou; Shujuan Yang; Riting Huang; Keyang Mai; Wenqi Qin; Junhao Huang; Gaobo Yu; Yuhong Feng; Jiacheng Li (Carbohydrate Polymers, 2023)

Light-tuning the host–guest interfacial recognition of Alginate-based amphiphiles for oil-in-water droplet deposition - Xinyu Zhao; Qu Zeng; Shujuan Yang; Furui He; Wenqi Qin; Zhaojun Wang; Keyang Mai; Gaobo Yu; Junhao Huang; Jiacheng Li; Yuhong Feng (Chemical Engineering Journal, 2023)

A time series model adapted to multiple environments for recirculating aquaculture systems - Gedi Liu; Yifeng Jiang; Keyang Zhong; Yan Yang; Yang Wang (Aquaculture, 2023)

Efficient selective adsorption of cytokine IL-6 and other middle-macromolecular toxins in the serum of uremia patients with specially designed porous hollow carbon spheres - Xiaohuan Zhao; Chong Wang; Boyang Xu; Jie Liang; Keyang Li; Yiqing Guo; Ming Gong; Yun Zhao; Yilun Huang; Yuehong Li; Ming Zhao; Daming Zhuang; et al. (Chemical Engineering Journal, 2023)

Current status of indoor dust PBDE pollution and its physical burden and health effects on children - Keyang Zheng; Zhijun Zeng; Yucong Lin; Qihua Wang; Qianwen Tian; Xia Huo (Environmental Science and Pollution Research, 2023)

In vitro simulated digestion of and microbial characteristics in colonic fermentation of polysaccharides from four varieties of Tibetan tea - Yaowen Tan; Meiwen Li; Keyang Kong; Yushan Xie; Zhen Zeng; Zhengfeng Fang; Cheng Li; Bin Hu; Xinjie Hu; Caixia Wang; Saiyan Chen; Wenjuan Wu; et al. (Food Research International, 2023)

Experimental Study on Unsteady Cavitating Flow and Its Instability in Liquid Rocket Engine Inducer - Hao Wang; Jian Feng; Keyang Liu; Xi Shen; Bin Xu; Desheng Zhang; Weibin Zhang (Journal of Marine Science and Engineering, 2022)
To study instability in the unsteady cavitating flow in a liquid rocket engine inducer, visualization experiments of non-cavitating and cavitating flows inside a model inducer were carried out at different flow conditions. Visual experiments were carried out to capture the evolution of non-cavitating and cavitating flows in a three-bladed inducer by using a high-speed camera. The external characteristic performance, cavitation performance, and pressure pulsation were analyzed based on the observation of non-cavitation and cavitation development and their instabilities. Under non-cavitation conditions, the change of flow rate has a significant impact on the pressure pulsation characteristics in the inducer. The occurrence of cavitation aggravated the instability of the flow and caused the intensity of pressure pulsation at each measuring point to increase. This cavitation structure has strong instability, and the tail region is often accompanied by shedding cavitation clouds perpendicular to the blade surface.

Multi-proxy evidence of environmental change related to collapse of the Liangzhu Culture in the Yangtze Delta, China - Keyang He; Houyuan Lu; Guoping Sun; Xiang Ji; Yonglei Wang; Kaikai Yan; Xinxin Zuo; Jiangping Zhang; Bin Liu; Ningyuan Wang (Science China Earth Sciences, 2021)

Association between serum amyloid A levels and coronary heart disease: a systematic review and meta-analysis of 26 studies - Jielin Zhou; Yao Lu; Sufang Wang; Keyang Chen (Inflammation Research, 2020)

Phytolith analysis for the identification of barnyard millet (Echinochloa sp.) and its implications - Yong Ge; Houyuan Lu; Jianping Zhang; Can Wang; Keyang He; Xiujia Huan (Archaeological and Anthropological Sciences, 2018)

Development and Translational Application of an Integrated, Mechanistic Model of Antibody-Drug Conjugate Pharmacokinetics - Siddharth Sukumaran; Crystal Zhang; Douglas D. Leipold; Ola M. Saad; Keyang Xu; Kapil Gadkar; Divya Samineni; Bei Wang; Marija Milojic-Blair; Montserrat Carrasco-Triguero; Bonnee Rubinfeld; Paul Fielder; et al. (The AAPS Journal, 2017)